2012
DOI: 10.1002/jemt.22038
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome observation by scanning electron microscopy using ionic liquid

Abstract: Electron microscopy has been used to visualize chromosome since it has high resolution and magnification. However, biological samples need to be dehydrated and coated with metal or carbon before observation. Ionic liquid is a class of ionic solvent that possesses advantageous properties of current interest in a variety of interdisciplinary areas of science. By using ionic liquid, biological samples need not be dehydrated or metal‐coated, because ionic liquid behaves as the electronically conducting material fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 23 publications
0
35
0
Order By: Relevance
“…Because of these properties, ionic liquids have proven advantageous for biological sample preparation prior to SEM observation. In addition, platinum blue (Pt-blue) staining enhanced the contrast of chromosome images (Dwiranti et al, 2012). The ionic liquid technique provides visualization closer to the native state since it enables us to observe biological samples without drying, dehydration, or metal/carbon coating.…”
Section: Introductionmentioning
confidence: 99%
“…Because of these properties, ionic liquids have proven advantageous for biological sample preparation prior to SEM observation. In addition, platinum blue (Pt-blue) staining enhanced the contrast of chromosome images (Dwiranti et al, 2012). The ionic liquid technique provides visualization closer to the native state since it enables us to observe biological samples without drying, dehydration, or metal/carbon coating.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Kuwabata et al (2006) showed that ILs could be observed by SEM without the electroncharge accumulation from the so-called charge-up effect, although ILs possess ionic conductivity. It was subsequently demonstrated that IL-treated specimens swollen with water could be observed by SEM without the laborious pretreatment processes (Arimoto et al, 2008c;Dwiranti et al, 2012;Ishigaki et al, 2011a, b, c;Takahashi et al, 2013;Tsuda et al, 2011b). These results led us to observe wet pollen grains treated with an IL under vacuum conditions.…”
Section: Introductionmentioning
confidence: 85%
“…For example, many types of ILs have been shown to exert antimicrobial activity. Another interesting application is to use ILs as a coating agent in scanning electron microscopy (SEM) of biological specimens . The nonvolatility of ILs makes it possible to observe SEM images of the specimen under wet conditions, and the high electronic conductivity of ILs prevents the specimen from charging.…”
Section: Introductionmentioning
confidence: 99%